Dual-fuel operation of gasoline and natural gas in a turbocharged engine. (1st February 2019) - Singh, Eshan; Morganti, Kai; Dibble, Robert
Abstract: Natural gas is a high-octane fuel that produces lower CO2 emissions per kilowatt hour than liquid transport fuels, with essentially zero sulfur emissions. Historically, natural gas has mostly been used in power generation and industrial applications. However, there has been a recent shift towards employing natural gas in the transport sector. In many regions, vehicles are retrofitted with compressed natural gas (CNG) systems, enabling operation on both gasoline and natural gas (and theoretical mixtures thereof). This work examines the effect of leveraging the secondary natural gas fuel system on the performance, efficiency and broader environmental impact of a high specific output gasoline engine. Firstly, mixture sweeps are presented for varying gasoline/natural gas ratios (100% gasoline to 100% natural gas) at wide open throttle (WOT) with both fixed and variable spark timing. This baseline information is then used to optimize the engine calibration for varying gasoline/natural gas ratios over a wider range of operating conditions. Finally, the CO2 -equivalent emissions are computed to investigate the broader environmental impact of an optimized gasoline/natural gas vehicle.